Surat Kuasa Membebankan Hak Tanggungan (SKMHT) Batal Demi Hukum: Urgensi dan alternatif membangun konsep baru perlindungan hukum bagi kreditor - Piters Djajakustio (Faculty of Law, University of Jember, Indonesia, 2023)
Time limitation regarding the validity of the power of attorney to impose mortgage rights or SKMHT in Article 15 paragraph 3 and 4 of the Law on Mortgage Rights is essentially a form of legal protection by the State as outlined in a statutory regulation. However the provision on the period of SKMHT imposes a relatively short, while on the other hand, the process of obtaining a land title certificate takes a long time does not provide legal protection for creditors and potentially creditors fail to obtain collateral. The imbalance ultimately does not reflect justice for creditor. The research method in this article is normative juridical, which is legal research that places law as a building system of norms. The norm system in question is regarding the principles, norms, rules of laws and regulations, court decisions, agreements and doctrines (teachings). Types of normative juridical research include legal principles, namely research on written positive laws or research on legal principles that live in society, sources of law, statutory regulations that are scientific theoretical in nature and can analyze the issues discussed. This study aims to examine the urgency of developing a new concept of legal protection for creditors due to SKMHT being null and void. KEYWORDS: SKMHT, Time Limit, Creditors